Analisis Pengaruh Pembiayaan Bank Syariah, PDRB, dan Pengeluaran Per Kapita terhadap Kemiskinan di Pulau Sumatera Tahun 2016-2021 - Riyani Butar Butar; Irsad Irsad; Ahmad Albar Tanjung; Sukardi Sukardi (Universitas Muhammadiyah Surabaya, 2023)
AbstractPoverty is a problem faced by all countries in the world, especially developing countries, such as Indonesia. Poverty is a complex problem that is influenced by various interrelated factors, including Islamic bank financing, economic growth, and per capita spending. This study aims to analyze how and how much influence the variables of Islamic bank financing, economic growth, and per capita expenditure have on the poverty rate on the island of Sumatra in 2016-2021. The analytical method in this study uses panel data regression analysis using the Random Effect Model (REM) which uses combined data between cross sections, namely 10 provinces on the island of Sumatra with the 2016-2021 time series with the help of Eviews 10 software. The results of this study indicate that the variable Islamic bank financing and expenditure per capita have a negative and significant effect on the level of poverty on the island of Sumatra. Meanwhile, the Economic Growth variable calculated through per capita GRDP has a positive and insignificant effect on the poverty rate on the island of Sumatra.Â Keywords: Poverty, Islamic Bank Financing, Economic Growth, per capita spending.